Karakteristik Pengeringan Biji Kopi Robusta pada Dua Metode Penjemuran - Dwi Dian Novita; Tamrin Tamrin; Siti Suharyatun; Asropi Asropi; Martha Riganda; Ahmad Tusi; Ridwan Ridwan (abe.fp.unila.ac.id, 2026)
Study on drying robusta coffee beans using a solar dryer dome was conducted to support the improvement of coffee bean quality in Lampung Province. This study aims to determine and compare the effects of thickness and drying methods (solar dryer dome and sun drying) on the drying characteristics of robusta coffee beans. The parameters observed were temperature, humidity, weight loss, moisture content, and drying rate. The research results indicate that the reduction in coffee bean moisture content in the solar dryer dome occurred more rapidly than with sun drying. The drying process took 10 days using the solar dryer dome method and 21 days using the sun drying method. ANOVA results on day 10 indicate that the variations in thickness and drying methods significantly affected the moisture content of the coffee beans. LSD results show that the effects of the treatments differed significantly from one another. The treatment using a solar dryer dome with a single-layer thickness yielded the lowest moisture content at 10.2% (wet basis).